An Integrated Risk Management Methodology for Deposits and Loans - Gregory R. Hackworth; Weidong Tian; Michael R. Vandenberg (Risks)
This paper presents an integrated risk management methodology for measuring and managing the economics, risks, and financial resources/constraints related to deposits and loans in a commercial bank. Within a comprehensive and integrated framework, we develop valuation and risk models for all financial products on the bank’s balance sheet. Our proposed methodology aligns with regulatory requirements while offering a practical implementation. Unlike traditional industry practices, which often rely on fragmented and siloed risk management solutions, our approach integrates risk modeling across all aspects of the bank’s balance sheet. This new perspective provides a more accurate and consistent assessment of financial risks, improving the bank’s ability to navigate regulatory and economic challenges.